Advisor: A system to develop and use online help. - Murphy, Mary Patricia. (University of Ottawa (Canada), 1990)
The purpose of this thesis is to create a tool (Advisor) for the development and use of online help systems. The study of human-computer interface issues is central to this task. In particular, attention has been given to the analysis of learning principles as related to interface strategies. The Advisor software is used by help designers to develop help systems and by application users to get assistance during applications use. It has two parts: the Designer (editor/outliner used by the help developer for help screen definition) and the Browser (help viewer used by the software end user for assistance from within an application). Using hypertext technology, the Advisory creates a tutorial environment where help screens and keyword links provide context sensitive help to assist the application user. A simple interface exists for access to the Browser by an application program.
Keywords: Computer Science.